Fathers as co-parents: how co- parenting perceptions are linked to Australian couples' sharing of childcare, other household work and paid work - Baxter, Jennifer (My University, 2013)
The way that parents co-parent is an important aspect of how couple families function. This coparental relationship includes sharing the unpaid work of raising a family and managing the household, communicating and sharing decision-making about childrearing, as well as providing support to each other in roles within and outside the family. This paper uses couple-level data to help gain an understanding of how the sharing of paid and unpaid work relates to parents' perceptions of the quality of the co-parental relationship. The aim is to provide new insights on what parents might consider to be a good co-parental relationship. Previous coparenting research has shown that coparenting processes might be different for mothers and for fathers, and this paper allows us to explore this, using family-level data in which reports of both mothers and fathers are available. This paper explores aspects of the coparental relationship using data from Growing up in Australia: the Longitudinal Study of Australian Children (LSAC). This paper makes use of the data collected in Wave 3 in 2008, from both cohorts, such that children were aged 4-5 years (the B cohort) or 8-9 years (the K-cohort) to make use of coparenting items that were only available in this wave.
Keywords: Families -- Parents and Parenting; Beliefs and Values -- Housework; Child Care; Families -- Fathers; Employment; Families and relationships; Labour market; Lifestyle; Beliefs and Values; Families; Employment; Child Care; Parents and Parenting; Housework; Fathers; Employment and unemployment; Families and relationships; Lifestyle